2022
DOI: 10.3390/soc12020039
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Competence in Healthcare Leadership Education and Development

Abstract: Cultural competence is a phenomenon that straddles many disciplines and fields of study. There is no settled definition of the term, and it is argued that this is not necessary to explore or discuss the phenomenon as it is context-dependent across diverse societies. Explorations of cultural competence in clinical education and training are well-established, but there has been less attention towards its expression in the field of developing healthcare leaders. There is a debate about whether cultural competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…We should certainly not forget that, in addition to doctors and nurses, non-medical personnel are also employed in health institutions. Patients also come into contact and interact with them every day, so it is necessary to include them in the work on cultural awareness, issues of diversity and power (Gulati et al, 2022).…”
Section: Health Workforce Cultural Competency Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…We should certainly not forget that, in addition to doctors and nurses, non-medical personnel are also employed in health institutions. Patients also come into contact and interact with them every day, so it is necessary to include them in the work on cultural awareness, issues of diversity and power (Gulati et al, 2022).…”
Section: Health Workforce Cultural Competency Interventionsmentioning
confidence: 99%
“…Cultural and linguistic competence in the provision of health care are two inseparable entities and represent a set of behaviors, attitudes and policies within the system and employees and enable effective work in intercultural circumstances (Gulati et al, 2022). Cultural competence is not determined only by the knowledge acquired during education and training, although the importance of this form of knowledge acquisition cannot be disputed, but it represents a constant commitment and awareness of cultural factors that influence attitudes about health and disease (Abubakar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no settled definition of the term, as it is argued that cultural competence straddles many disciplines. 4 As defined by Govender et al, 5 cultural competence is the process by which individuals and systems respond respectfully and effectively to people of all cultures, languages, classes, races and ethnic backgrounds in a way that recognizes, affirms, and values the worth of the individual and protects and preserves the dignity of each. …”
Section: Introductionmentioning
confidence: 99%
“…In their article about "cultural competence in healthcare leadership education and development", Gulati and Weir [22] explained that cultural competence should not be approached the same way across disciplines and professions but should be understood and used in specific contexts. By exploring the relevant literature and leadership development programmes in the English National Health Service, Gulati and Weir concluded that in addition to awareness about cultures space for reflection, skills of reflexivity and discussion were essential for building cultural competencies in healthcare education leadership.…”
mentioning
confidence: 99%